Counting Immigrants and Expatriates in OECD Countries A New Perspective - Dumont, Jean-Christophe (OECD Publishing, 2006)
Since the end of the 1990s, issues related to international migration, and more particularly to the international mobility of highly-qualified workers, are receiving increasing attention from policy-makers. This reflects among others the increasing international movements that have been taking place following the fall of the Iron Curtain and in conjunction with the growing globalisation of economic activity. In addition, demographic imbalances between developed and developing countries and large differences in wages have tended to encourage the movements of workers from economies where they are in surplus to those where they are most in need.....